A new generalization of alpha-skew-normal distribution. Issue 12 (18th June 2017) - Sharafi, Maryam; Sajjadnia, Zahra; Behboodian, Javad
ABSTRACT: In this paper, a new generalization of alpha-skew-normal distribution is considered. Some properties of this distribution, which is denoted by GASN (α, λ), including moments, maximum likelihood estimation of parameters, and some other properties are studied. Finally, using a real data set, we show that our new distribution is the best-fitted distribution for the used data among normal, skew normal, alpha-skew-normal, and skew-bimodal-normal distributions.